Shifting Out of “Neutral”: Beginning Teachers’ Struggles with Teaching for Social Justice - Kelly, Deirdre; Brandes, Gabriella (Canadian Journal of Education/Revue canadienne de l’éducation, 2001)
In this article we explore the struggles of 12 beginning teachers committed to social justice to define their roles when facilitating classroom discussions of social issues. We discerned five distinct positions about the possibility and desirability of teacher neutrality. To teach for social justice involves shifting out of neutral, both in terms of a teacher’s orientation to social inequalities and of pedagogy. Our preferred teacher role, inclusive and situated engagement, involves spotlighting the perspectives of subordinated groups and providing opportunities for young people to develop their deliberative capacities and to learn to act on their reasoned convictions. L’article porte sur douze enseignants débutants soucieux de justice sociale et cherchant à définir leurs rôles dans les discussions en classe sur des questions sociales. Cinq positions distinctes au sujet de la possibilité et de l’opportunité de la neutralité de l’enseignant sont examinées. Un enseignement axé sur la justice sociale implique que l’enseignant sorte de la neutralité quant à son orientation vis-à-vis des inégalités sociales et de la pédagogie. Les auteures privilégient l’engagement inclusif et situationnel, l’enseignant mettant en lumière les points de vue des groupes marginalisés et fournissant aux jeunes l’occasion de développer leur aptitude à délibérer et d’apprendre à agir à partir de convictions éclairées.